Quantitative Analysis of the Meteorological Data and their Implication for Geo-Environmental Classification Map of the Nineveh Governorate - AL_Daghastani, Hekmat; yahya, Basher (Iraqi Journal of Science, 2024)
Given the close interrelationship between the manifestations of geomorphological landforms and land use and land cover on the one hand and quantitative analysis of the Meteorological data and its implications on the classification map of the Governorate of Nineveh, on the other, was in the present study rely on the basic elements used in the style of the interpretation of visualization space successive time providing a main pillar for the diagnosis of some environmental problems, which began to suffer from Nineveh Governorate over time.Evidence suggests many of the elements in the analysis of climate change for the period (1974-2010) to speed up the processes of desertification and environmental budget imbalance of vegetation, which reflected negatively on the composition of dust storms and their conformity with the current reality of the geo-environmental classification map for the Governorate.